1993
DOI: 10.1039/ft9938901871
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-phase adsorption of monosaccharide–water mixtures on X and Y zeolites

Abstract: A systematic study has been performed on the adsorption of o-fructose-, D-glucose-and D( -)-arabinose-water mixtures on K+, Sr2+, Ca2+, Ba2+ and La3+ ion-exchanged X and Y zeolites. From the adsorption excess isotherms the separation factors K and the equilibrium diagrams x; vs. x i of the binary mixtures were calculated. The possible triangles of 0 atoms of monosaccharides, their interactions with cations, the influence of crystallographic cation positions and the Si : Al ratio of zeolites on formation of ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…8 In these cases the zeolite was exchanged with alkali and alkalineearth metal ions, and the specific interactions with different sugars were small but depending on the nature of the counterion. 9,10 The following presentation deals with the real adsorption of carbohydrates from the liquid phase which means that the saccharide molecules are enriched in the pores of the zeolite. High specific adsorption of carbohydrates on hydrophobic Y-zeolites with only negligible fraction of ionic sites has already been reported, 11 and also beta zeolites were shown to have similar effects.…”
Section: Introductionmentioning
confidence: 99%
“…8 In these cases the zeolite was exchanged with alkali and alkalineearth metal ions, and the specific interactions with different sugars were small but depending on the nature of the counterion. 9,10 The following presentation deals with the real adsorption of carbohydrates from the liquid phase which means that the saccharide molecules are enriched in the pores of the zeolite. High specific adsorption of carbohydrates on hydrophobic Y-zeolites with only negligible fraction of ionic sites has already been reported, 11 and also beta zeolites were shown to have similar effects.…”
Section: Introductionmentioning
confidence: 99%
“…The broadening of the elution profile results from mass transfer resistances or limitations in reaction kinetics [53], indicating that these are more pronounced with the dehydrated sample than for the hydrated samples. This may originate from the difference in cation location within the X zeolite framework structure between the hydrated and dehydrated state [94] and/or the absence of water which may promote the HCl (reactive) uptake, rather than a degradation of the material structure due to the activation. XRD reveals that the dried material after contact with HCl preserved the (crystalline) characteristics of the native material (Fig.…”
Section: Effect Of Zeolite Hydrationmentioning
confidence: 99%
“…In the few batch system studies [7,8] Henry's constants were determined but adsorption capacities were not reported. Buttersack et al [7] studied dealuminated zeolite Y and found that Si/Al ratio of the zeolite had significant influence on the selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Buttersack et al [7] studied dealuminated zeolite Y and found that Si/Al ratio of the zeolite had significant influence on the selectivity. In another study reported by Schöllner et al [8] Na-X and Na-Y zeolites were ion exchanged with K + , Sr 2+ , Ca 2+ , Ba 2+ , and La 2+ and their adsorption excess isotherms and equilibrium diagrams of binary mixtures were determined. It was shown that the amount of adsorbed fructose also increased as the amount of exchanged Ca 2+ was increased [8].…”
Section: Introductionmentioning
confidence: 99%